Concordance of biopsy and prostatectomy diagnosis of intraductal and cribriform carcinoma in a prospectively collected data set. Issue 3 (4th November 2018) - Masoomian, Mehdi; Downes, Michelle R; Sweet, Joan; Cheung, Carol; Evans, Andrew J; Fleshner, Neil; Maganti, Manjula; Van der Kwast, Theodorus
Abstract : Aims: Intraductal and cribriform carcinoma of the prostate are increasingly recognised as independent prognosticators of poor outcome, both in prostate biopsies and surgical specimens. We studied the concordance of biopsy and prostatectomy diagnosis for these two subpathologies in relationship with pathological stage. Methods and results: Mandatory synoptic reporting of intraductal and cribriform carcinoma in prostate biopsies and prostatectomy specimens was adopted by two academic institutions in November 2015. Synoptic reports of 245 biopsy and corresponding prostatectomy specimens were interrogated to determine the prevalence of intraductal and cribriform carcinoma. Sensitivity and specificity were determined, with prostatectomy diagnosis as the gold standard. Associations with pathological stage as primary outcome parameter were determined using univariable and multivariable logistic regression analysis. Prevalence of the combination of intraductal and cribriform carcinoma was 26.9% in biopsies and 51.8% in prostatectomy specimens. Sensitivity and specificity at biopsy were 47.2% and 94.9%, respectively. Intraductal and cribriform carcinoma at biopsy were associated with advanced pathological stage independent of grade ( P = 0.013). Among patients with grade group 2 prostate cancer at biopsy, the more advanced pathological stage distribution was similar for those with a false negative and a true positive biopsy diagnosis of intraductal and cribriform carcinoma ( P = 0.29). Conclusion: In spite of low sensitivity, intraductal and cribriform carcinoma at biopsy was associated strongly with advanced stage at radical prostatectomy. As a false negative biopsy diagnosis was equally associated with advanced pathological stage, efforts should be undertaken to improve the sensitivity of biopsy diagnosis for intraductal and cribriform carcinoma.